2020
DOI: 10.1002/ejp.1645
|View full text |Cite
|
Sign up to set email alerts
|

Pain‐autonomic interaction: A surrogate marker of central sensitization

Abstract: Background: Central sensitization represents a key pathophysiological mechanism underlying the development of neuropathic pain, often manifested clinically as mechanical allodynia and hyperalgesia. Adopting a mechanism-based treatment approach relies highly on the ability to assess the presence of central sensitization. The aim of the study was to investigate potential pain-autonomic readouts to operationalize experimentally induced central sensitization in the area of secondary hyperalgesia. Methods: Pinprick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 57 publications
6
29
0
Order By: Relevance
“…In experimental pain assessment, the pain response is often recorded via different output channels, because these are not necessarily consistent within an individual (Cowen et al, 2015; Scheuren et al, 2020). Thus, in addition to subjective self‐report of pain, other more objectively measurable methods, such as electrodermal activity (EDA) as a proxy for autonomic nervous system (ANS) dynamics (Posada‐Quintero & Chon, 2020), are integrated.…”
Section: Introductionmentioning
confidence: 99%
“…In experimental pain assessment, the pain response is often recorded via different output channels, because these are not necessarily consistent within an individual (Cowen et al, 2015; Scheuren et al, 2020). Thus, in addition to subjective self‐report of pain, other more objectively measurable methods, such as electrodermal activity (EDA) as a proxy for autonomic nervous system (ANS) dynamics (Posada‐Quintero & Chon, 2020), are integrated.…”
Section: Introductionmentioning
confidence: 99%
“…Central sensitization, an important feature of migraine, 47 has recently been demonstrated in patients with POTS (both with and without migraine) and may be a significant shared pathophysiology 48 . Central sensitization in POTS and migraine may involve elevations in pro‐inflammatory cytokines 47,49 as well as interactions between pain and autonomic circuitry 50 …”
Section: Migraine and Pots Pathophysiologymentioning
confidence: 99%
“…48 Central sensitization in POTS and migraine may involve elevations in pro-inflammatory cytokines 47,49 as well as interactions between pain and autonomic circuitry. 50 As discussed in section 2.0, post-ganglionic sympathetic denervation and augmented activity of the sympatho-adrenal medullary axis contribute to the development of neurogenic and hyperadrenergic POTS, respectively. There is emerging evidence that similar pathology exists in people with migraine.…”
Section: Pathophysiology In Pots and Migrainementioning
confidence: 99%
“…In SCI, the assessment of TSP has been performed using repetitive phasic (Defrin et al, 2001;Eide et al, 1996;Konopka et al, 2012) and tonic (Albu et al, 2015;Gruener et al, 2016;Scheuren et al, 2019) noxious stimuli. Generally, studies found a higher occurrence and magnitude of TSP in subjects with SCI with NP (SCI-NP) compared to those without (SCI-nonNP) and healthy controls (HC) (Defrin et al, 2001;Gruener et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Common denominators are an initial decrease of pain rating, i.e. adaptation (Gruener et al, 2016;Scheuren et al, 2019), followed by a subsequent increase, i.e. TSP, the latter potentially reflecting spinal sensitization, i.e.…”
Section: Introductionmentioning
confidence: 99%